Chalcopyrite Leaching in Ammonia-Ammonium Chloride Solutions: Insight into the Dissolution Kinetic Studies - Y. Chindo, Shemang; I. Omoniyi, Kehinde; A. Raji, Mustapha (Journal of Sustainable Materials Processing and Management, 2022)
The hydrometallurgical method for processing chalcopyrite ore has gained enormous attention due to the environmental problems emanated by the conventional pyrometallurgical route. Here, hydrometallurgy is considered an alternative that may be more of low-cost and environmentally friendly. Thus, alkaline leaching has been considered an effective, efficient, and acceptable leachant for chalcopyrite ore dissolution. The dissolution kinetics of copper from low-grade chalcopyrite ore was examined in an ammonia-ammonium chloride solution. However, the effect of parameters including leachant concentration, reaction temperature, and particle size was considered. . At optimal conditions (o.4 mol/L NH3-NH4Cl; 75 °C; 43 µm), 81.1% dissolution efficiency was achieved within 120 minutes. The leaching kinetics with activation energy (Ea) of 29.95 kJ/mol is by the proposed diffusion control mechanism. Hence, the dissolution rate was confirmed by characterizing the raw ore and un-leached residue using XRD and SEM-EDS analyses for possible industrial utilities.